2022
DOI: 10.1186/s12870-022-03879-0
|View full text |Cite
|
Sign up to set email alerts
|

Between allopatry and secondary contact: differentiation and hybridization among three sympatric Gentiana species in the Qinghai-Tibet Plateau

Abstract: Background Mountains of the world host a significant portion of all terrestrial biodiversity, and the region of the Qinghai-Tibet Plateau (QTP) stands as one of the most remarkable mountain regions on Earth.  Because many explosive radiations occurred there, the QTP is a natural laboratory which is ideal to investigate patterns and processes linked to speciation and diversification. Indeed, understanding how closely related and sympatric species diverged is vital to explore drivers fostering sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Although the Bayankala Mountains are not characterized by high ruggedness as the HM, their average elevation of approximately 5000 m makes them sufficient to serve as barriers throughout glacial cycles for species like Gentiana aristata with short-distance dispersal pollinators. Recently, a set of studies on plants from the QTP region, including Pinus armandii ( Liu et al., 2019 ), Rheum palmatum ( Feng et al., 2020 ), and Gentiana hexaphylla ( Fu et al., 2022b ), identified a distinct genetic pattern in this topographically complicated environment. These geographical characteristics also had an important impact on species assembly across the HM and the greater QTP region ( Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Bayankala Mountains are not characterized by high ruggedness as the HM, their average elevation of approximately 5000 m makes them sufficient to serve as barriers throughout glacial cycles for species like Gentiana aristata with short-distance dispersal pollinators. Recently, a set of studies on plants from the QTP region, including Pinus armandii ( Liu et al., 2019 ), Rheum palmatum ( Feng et al., 2020 ), and Gentiana hexaphylla ( Fu et al., 2022b ), identified a distinct genetic pattern in this topographically complicated environment. These geographical characteristics also had an important impact on species assembly across the HM and the greater QTP region ( Li et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The QTP region serves as both the center of biodiversity for approximately 360 Gentiana species ( Ho and Liu, 2001 ) and the primary source for colonization of other regions ( Favre et al., 2016 ). As observed in the majority of plant lineages, abiotic factors, including geological processes, geographical isolation, and climatic changes, are correlated with diversification and speciation in several lineages of Gentiana ( Zhang et al., 2009 ; Favre et al., 2016 ; Fu et al., 2018 , 2020 , 2022b ; Sun et al., 2022 ). In addition, according to growing evidence from phylogenetic and population genetic studies, hybridization is frequently observed in Gentiana , both in the QTP region ( Chen et al., 2021 ; Fu et al., 2021a , 2022a ) and Europe ( Favre et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%